THE APPLICATION OF INDEX CARD MATCH METHODS WITH CONCRETE MEDIA IN IMPROVING NATURAL SCIENCE LEARNING ABOUT STYLE AT FIFTH GRADE STUDENTS OF SDN 1 PANJER IN THE ACADEMIC YEAR OF 2014/2015. - Setyaji, Ridwan Hermawan (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract. The Application Of Index Card Match Methods with Concrete Media In Improving Natural Science Learning about Style At Fifth Grade Students Of SDN 1 Panjer In The Academic Year of 2014/2015. The objectives of this study to determine the increase of natural science learning about style through the application of Index Card Match method with concrete media at the fifth grade students of SDN 1 Panjer in academic year of 2014/2015. This study is a collaborative Classroom Action Research (CAR) implemented in three cycles, with each cycle consisting of two meetings of planning, implementation, observation, and reflection. The subjects were fifth grade students of SD Negeri 1 Panjer, amounting to 24 students. The result of this study indicate the application Index Card Match Methods with concrete media can inprove natural science learning about style at the fifth grade students of SDN 1 Panjer in academic year of 2014/2015. Keywords: Index Card Match, Concrete Media, Natural Science learning Abstrak. Penerapan Metode Index Card Match dengan Media Konkret dalam Peningkatan Pembelajaran IPA pada Siswa Kelas V SDN 1 Panjer Tahun Ajaran 2014/2015. Tujuan dari penelitian ini adalah untuk mengetahui peningkatkan pembelajaran IPA tentang gaya melalui metode Index Card Match dengan media konkret pada siswa kelas V SDN 1 Panjer tahun ajaran 2014/2015. Penelitian ini merupakan penelitian tindakan kelas (PTK) kolaboratif yang dilaksanakan dalam tiga siklus, dengan tiap siklus terdiri dari dua pertemuan yang terdiri dari perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian ini adalah siswa kelas V SDN 1 Panjer yang berjumlah 24 siswa. Hasil penelitian ini menunjukkan bahwa penerapan metode Index Card Match dengan media konkret dapat meningkatkan pembelajaran IPA tentang gaya pada siswa kelas V SDN 1 Panjer tahun ajaran 2014/2015. Kata Kunci: Index Card Match, media konkret, pembelajaran IPA.